Etymological Considerations on Polish Colloquial Vocabulary - Witczak, Krzysztof Tomasz (Papers in Linguistics, 2025)
The article critically discusses twelve entries in the recently published Etymological Dictionary of Colloquial Polish PWN by Adam Fałowski (Warszawa 2022). The conducted etymological analysis demonstrated that Polish colloquial vocabulary functioning in environmental or regional jargons has a very complex and heterogeneous origin. Among the reviewed words are German or Jewish (Yiddish) borrowings (e.g. Pol. ciumkać, cumelek, cymes, ćwik, flejtuch, kunda, kundel), French (e.g. Pol. dyrdymała), Hungarian (e.g. Pol. fiut), as well as Modern Greek loanwords adopted through the Polish-Ruthenian argot of the Ochweśnicy (e.g. Pol. bulić, troić), and even Iranian item borrowed via the East Slavic languages (e.g. Pol. szamać).